2017
DOI: 10.1103/physrevb.96.121406
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Dirac cones

Abstract: Physics arising from two-dimensional (2D) Dirac cones has been a topic of great theoretical and experimental interest to studies of gapless topological phases and to simulations of relativistic systems. Such 2D Dirac cones are often characterized by a π Berry phase and are destroyed by a perturbative mass term. By considering mean-field nonlinearity in a minimal two-band Chern insulator model, we obtain a novel type of Dirac cones that are robust to local perturbations without symmetry restrictions. Due to a d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 67 publications
4
47
0
Order By: Relevance
“…It is obtained by measuring the long-time average of chiral displacement operator Sn, where S is the unitary and Hermitian operator that defines the chiral symmetry of the system, andn is the unit cell position operator. The MCD was first proposed for 1d non-driven systems in the symmetry classes AIII and BDI [90], and later extended to Floquet systems [61,91], non-Hermitian systems [52,53] and systems in two dimensions [46]. In this work, we further extend the MCD to 1d Floquet systems in the symmetry class CII, and employ it to probe the topological phases of the PQSCL dynamically.…”
Section: Dynamical Probesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is obtained by measuring the long-time average of chiral displacement operator Sn, where S is the unitary and Hermitian operator that defines the chiral symmetry of the system, andn is the unit cell position operator. The MCD was first proposed for 1d non-driven systems in the symmetry classes AIII and BDI [90], and later extended to Floquet systems [61,91], non-Hermitian systems [52,53] and systems in two dimensions [46]. In this work, we further extend the MCD to 1d Floquet systems in the symmetry class CII, and employ it to probe the topological phases of the PQSCL dynamically.…”
Section: Dynamical Probesmentioning
confidence: 99%
“…On application side, Floquet states have the potential of realizing setups with many topological transport channels [40][41][42] and creating new schemes of topological quantum computations [43][44][45]. In recent years, the study of Floquet topological matter has also been extended to higher-order topological models [46][47][48][49][50] and non-Hermitian systems [51][52][53][54][55][56][57][58].…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, the hexagonal lattice is also amazing because it has two sites per unit cell (say, A-site and B-site), so this system can be described by the two-band model. Earlier studies [49,50] have shown that a self-crossing loop would exist in one-dimensional system and a nonlinear two-band model would develop a looped band structure. In the following, we will discuss the dependence of the looped structure [51,52] on the parameters of the system, and shed more light on the nonlinear Dirac cone (NDC) [50] in this two-dimensional system.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies [49,50] have shown that a self-crossing loop would exist in one-dimensional system and a nonlinear two-band model would develop a looped band structure. In the following, we will discuss the dependence of the looped structure [51,52] on the parameters of the system, and shed more light on the nonlinear Dirac cone (NDC) [50] in this two-dimensional system. We find that there are two NDCs in the Brillouin Zone (BZ), and the phase acquired by adiabatically transporting the system on the lowest band around the two NDCs in the BZ is zero, while the phase acquired in the same processing is quantized around only one of the NDCs.…”
Section: Introductionmentioning
confidence: 99%
“…Introducing Kerr nonlinearity, using the soliton solution () we derive the edge states' nonlinear dispersion 0trueω=normalΔωN-0.16emLk0.222222em,1emnormalΔωN-0.16emL=g2ρs()αs=±π4which undergoes a shift in the band gap [M0,M0]. The valley Chern number formally stays the same as its linear counterpart until the upper band of nonlinear Bloch waves forms a self‐crossing loop at above‐threshold bulk intensities I2M0 . Thereby, nonlinearity grants control over the frequency and transverse structure of the edge state as defined by ρsfalse(αsfalse).…”
mentioning
confidence: 99%